Contrasting behavior of the p18(INK4c) and p16(INK4a) tumor suppressors in both replicative and oncogene-induced senescence - Gagrica, Sladjana (Cancer Res, 2011)
The CDK inhibitors, p18(INK4c) and p16(INK4a), both have the credentials of tumor suppressors in human cancers and mouse models. For p16(INK4a), the underlying rationale is its role in senescence but the selective force for inactivation of p18(INK4c) in incipient cancer cells is less clear. Here we show that in human fibroblasts undergoing replicative or oncogene-induced senescence, there is a marked decline in the levels of p18(INK4c) protein and RNA, which mirrors the accumulation of p16(INK4a). Down-regulation of INK4c is not dependent on p16(INK4a) and RAS can promote the loss of INK4c without cell cycle arrest. Down-regulation of p18(INK4c) correlates with reduced expression of menin and E2F1 but is unaffected by acute cell cycle arrest or inactivation of the retinoblastoma protein (pRb). Collectively, our data question the idea that p18(INK4c) acts as a backup for loss of p16(INK4a) and suggest that the apparent activation of p18(INK4c) in some settings represents delayed senescence rather than increased expression. We propose that the contrasting behavior of the two very similar INK4 proteins could reflect their respective roles in senescence versus differentiation.